Sex Differences in High-Intensity Interval Training–Are HIIT Protocols Interchangeable Between Females and Males? - Schmitz, Boris; Niehues, Hannah; Thorwesten, Lothar; Klose, Andreas; Krüger, Michael; Brand, Stefan-Martin (Frontiers in Physiology, 2020)
Background: High-intensity interval training (HIIT) is a well-established training modality to improve aerobic and anaerobic capacity with high efficiency. However, sex- and gender-specific aspects of different HIIT protocols are incompletely understood. This study aimed to investigate if HIIT protocols can be used interchangeably by moderately trained unmatched females and males in a real-world design. Methods: Fifty moderately trained participants (30 females, 20 males) performed an exercise field test and were randomized by individual anaerobic lactate threshold (IAT) to one of two time- and workload-matched training groups. Participants performed a 4-week HIIT intervention with two exercise sessions/week: Group 1 (4x30:180 HIIT), 30-s all-out runs, 180 s active recovery, Group 2 (4x30:30 HIIT), 30-s all-out runs, 30 s active recovery. High-intensity runs during training sessions were recorded and speed per running bout, average speed per session and speed decrement were determined. Blood lactate measurements were performed at baseline and follow-up. Results: Females and males differed in running speed at IAT and maximal running speed determined during exercise field test (speed at IAT, females: 10.65 ± 0.84 km∙h-1, males: 12.41 ± 0.98 km∙h-1, p<0.0001; maximal speed, females: 14.55 ± 1.05 km∙h-1, males: 17.41 ± 0.68 km∙h-1, p<0.0001). Analysis of HIIT protocols revealed an effect of sex on change in speed decrement (baseline vs. follow-up) in that females showed significant improvements only in the 4x30:30 HIIT group (p=0.0038). Moreover, females performing the 4x30:30 protocol presented increased speed per bout and average speed per session at follow-up (all p≤0.0204), while no effect was detected for females performing the 4x30:180 protocol. Peak blood lactate levels increased in all HIIT groups (all p<0.05, baseline vs. follow-up) but males performing the 4x30:180 protocol showed no difference in peak lactate levels. Conclusions: If not matched for physical performance, females, but not males, performing a 4x30 HIIT protocol with shorter recovery periods (30 s) present increased average high-intensity running speed and reduced speed decrement compared to longer recovery periods (180 s). We conclude that interchangeably of HIIT protocols between females and males may be restricted by sex- or gender-specific aspects in a real-world setting.